2015
DOI: 10.1016/j.drugalcdep.2015.07.018
|View full text |Cite
|
Sign up to set email alerts
|

Differential profiles of drug-addicted patients according to gender and the perpetration of intimate partner violence

Abstract: According to the results obtained, treatment programs for drug addiction are a suitable context for identifying the presence of IPV, but IPV is typically unnoticed in addiction treatment programs. The implications of these results for future research and clinical practice are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 35 publications
(33 reference statements)
0
8
0
Order By: Relevance
“…Bennett & Williams, 2003; Foran & O’Leary, 2008; Langenderfer, 2013; World Health Organization, 2010) but also is one important predictor of both IPV perpetrators’ treatment attrition and recidivism (e.g., Bowen & Gilchrist, 2006; Cadsky et al, 1996; Daly & Pelowski, 2000; Hilton & Harris, 2005; Olver, Stockdale, & Wormith, 2011; for a review, see Jewell & Wormith, 2010). The strong association between alcohol abuse and IPV perpetration is well illustrated by the fact that about 50% of IPV perpetrators referred to BIPs have some alcohol abuse problems (AAPs; Arteaga, López-Goñi, & Fernández-Montalvo, 2015; O’Farrell, Van Hutton, & Murphy, 1999; Stuart, Moore, Kahler, & Ramsey, 2003; Stuart, O’Farrell, & Temple, 2009). The strong link between alcohol abuse and IPV led the World Health Organization (2010) to recommend the reduction of alcohol abuse through prevention interventions as a strategy to reduce IPV.…”
mentioning
confidence: 99%
“…Bennett & Williams, 2003; Foran & O’Leary, 2008; Langenderfer, 2013; World Health Organization, 2010) but also is one important predictor of both IPV perpetrators’ treatment attrition and recidivism (e.g., Bowen & Gilchrist, 2006; Cadsky et al, 1996; Daly & Pelowski, 2000; Hilton & Harris, 2005; Olver, Stockdale, & Wormith, 2011; for a review, see Jewell & Wormith, 2010). The strong association between alcohol abuse and IPV perpetration is well illustrated by the fact that about 50% of IPV perpetrators referred to BIPs have some alcohol abuse problems (AAPs; Arteaga, López-Goñi, & Fernández-Montalvo, 2015; O’Farrell, Van Hutton, & Murphy, 1999; Stuart, Moore, Kahler, & Ramsey, 2003; Stuart, O’Farrell, & Temple, 2009). The strong link between alcohol abuse and IPV led the World Health Organization (2010) to recommend the reduction of alcohol abuse through prevention interventions as a strategy to reduce IPV.…”
mentioning
confidence: 99%
“…The same meta-analysis also found that greater drugrelated problem severity was associated with increased risk for IPV perpetration (Cafferky et al, 2018). In fact, among individuals seeking treatment for substance use, those who report IPV display more severe drug use problems (Arteaga et al, 2015;Schumm et al, 2018).…”
Section: Ipv and Drug Usementioning
confidence: 81%
“…Researchers have consistently found an association between drug abuse and IPV perpetration (Arteaga et al, 2015;Epstein-Ngo et al, 2014;Smith et al, 2012;Stith et al, 2004;Taft et al, 2010). For example, among a nationally representative sample of 530 married or cohabitating men, those with a lifetime diagnosis of alcohol or substance abuse or dependence were almost two times more likely to perpetrate physical IPV than men without alcohol/substance abuse or dependence (Singh, Tolman, et al, 2014).…”
Section: Drug Use and Ipv Perpetrationmentioning
confidence: 99%